Разработка алгоритма автоматического проектирования и оптимизации энергетического оборудования отопительной котельной - Збараз, Леонид Иосифович; Ганжа, А. Н.; Павлова, Виктория Геннадьевна (Национальный технический университет "Харьковский политехнический институт", 2017)
У даній роботі проаналізовані кілька варіантів компонування енергетичного обладнання котельної, визначено планові витрати енергоресурсів і обрано варіант з мінімальними прямими витратами за опалювальний сезон. На етапі проектування опалювальної котельної доцільно методами математичного моделювання змоделювати роботу обладнання і розглянути оптимальні варіанти установки котлів різної потужності. Це дозволить знизити прямі витрати при експлуатації в опалювальному сезоні і раціонально використовувати теплову потужність обладнання.

Several variants for the layout of the boiler equipment are analyzed in this paper. Also, the planned costs of energy resources are determined. The variant that provides the minimum direct costs for the heating season is chosen. Methods of mathematical modeling are recommended at the design stage for the selection of boilers with different capacities in order to choose the best variant. This allows to reduce direct costs during operation in the heating season and to use rationally the thermal capacity of the equipment.
Development of heating boiler house energy equipment automatic design and optimization algorithm
Keywords: котел; нагрузки; энергоресурсы; температурный график; отопительный сезон; КПД